Analisis Pengaruh Jumlah Uang Beredar Terhadap Petumbuhan Ekonomi di Indonesia - Exsan Landung Panggalih; Lusmino Basia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Economic growth is a problem in the short-term economy and long term and is influenced by various factors. This research was conducted to analyze the effect of money supply, exchange rates, investment and interest rates on economic growth in Indonesia. on economic growth in Indonesia. In this study using the method ARDL (Autoregressive Distributed Lag) analysis method. For the purpose of analysis used secondary data For the purpose of analysis used secondary data (time series) with vulnerable time 1990 -2023 includes data on economic growth, money supply, exchange rate / exchange rate, and interest rates on economic growth. economic growth, money supply exchange rate / exchange rate, investment and interest rates. Based on data processing, it is obtained that the money supply and exchange rates, and interest rates in the short term have a positive influence on economic growth. interest rates in the short term have a positive and significant effect on economic growth, while investment in the short term has a positive and significant effect on economic growth. economic growth, while investment in the short term has a negative and significant effect on economic growth. negative and significant, but in the long run the money supply and interest rates have a significant negative effect, and the value of investment in the short term has a significant negative effect. interest rates have a significant negative effect, and exchange rates and investment have a significant positive effect on economic growth. significant positive effect on Indonesia's economic growth in 1990-2023.